Mother‐to‐child transmission of hepatitis B: Examining viral cut‐offs, maternal HBsAg serology and infant testing. (31st March 2018) - Thilakanathan, Cynthuja; Wark, Gabrielle; Maley, Michael; Davison, Scott; Lawler, Joseph; Lee, Aimei; Shackel, Nicholas; Nguyen, Vi; Jackson, Kathy; Glass, Anne; Locarnini, Stephen A.; Levy, Miriam T.
Abstract: Background & Aims: Antipartum antiviral therapy in the setting of high viral load is recommended to prevent mother‐to‐child transmission of hepatitis B although recommended viral load cut‐offs vary. Quantitative HBsAg has been proposed as an alternative screening strategy to identify high viral load in this setting. Guidelines suggest testing all infants for vaccine response and infection. We set out to re‐examine viral load cut‐offs; the predictive value of quantitative HBsAg and the need for follow‐up infant testing in our cohort. Methods: A retrospective cohort study of 469 HBsAg positive mother‐baby pairs from 2 tertiary hospitals in Sydney was performed. Antiviral therapy (lamivudine or tenofovir disoproxil fumarate) was offered to women with viral load ≥6 log10 IU/mL (high) from 32 weeks gestation. Transmission and vaccine response was analysed according to viral load. The utility of quantitative HBsAg in identifying high viral load was examined. Results: Mother‐to‐child transmission only occurred in setting of high viral load, in 0.85% (1/117) of those who received antiviral therapy and in 8.66% (2/23) of those who chose not to. Quantitative HBsAg did not accurately identify high‐risk mothers HBV DNA ≥6 log10 IU/mL. Successful infant vaccine response was 98.7% overall, and 99.4% when viral load was <6 log10 IU/mL. Conclusion: Antiviral therapy initiated at 32 weeks when maternal viral load is ≥6 log10 IU/mL almost completely abrogates transmission. Quantitative HBsAg does not reliably predict high viral load. When maternal viral load is <6 log10 IU/mL, high vaccine efficacy and zero transmission suggests testing infants is of little value. Abstract : See Editorial on Page1177